CERTOLIZUMAB PEGOL IN THE TREATMENT OF AXIAL SPONDYLOARTHRITIS - Sh. F. Erdes (Научно-практическая ревматология)
The paper gives the results of the RAPID-axSpA study that has evaluated for the first time the efficacy of the tumor necrosis factor-α (TNF-α) inhibitor certolizumab pegol (CZP) in treatment of axial spondyloarthritis (axSpA) clinical forms: already developed ankylosing spondylitis and non-radiographic axSpA. CZP was shown to be effective in all forms of axSpA, whether radiographically detected sacroiliitis was present or absent. This study has also demonstrated for the first time the long-term efficacy of TNF-α inhibitors in patients with initially high C-reactive protein level and/or signs of active sacroiliitis by magnetic resonance imaging.